2021
DOI: 10.1002/erv.2847
|View full text |Cite
|
Sign up to set email alerts
|

Irritable bowel syndrome and functional dyspepsia in patients with eating disorders ‐ a systematic review

Abstract: Objectives: The prevalence of eating disorders is rising worldwide. The low body weight in anorexia nervosa as well as the increase in body mass index due to binge eating disorder are contributing to a strikingly high morbidity and mortality. In a similar pattern, the prevalence and burden of the disease of functional gastrointestinal disorders such as functional dyspepsia and irritable bowel syndrome is increasing. As gastrointestinal complaints are commonly reported by patients with eating disorders, the que… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 101 publications
0
10
0
1
Order By: Relevance
“…A la vez, no hallaron una asociación significativa entre el subtipo de SII y la puntuación de EAT (p > 0,05). Sin embargo, la intensidad y la duración del SII presentaron una correlación positiva con las puntuaciones de EAT, lo que justifica algunos comentarios de otros autores en los que se vincula la presencia de SII con alimentación desordenada e incluso con trastornos alimenticios como anorexia nerviosa, bulimia y trastornos no especificados (44) .…”
Section: Recomendaciones Dietéticas En Síndrome De Intestino Irritableunclassified
“…A la vez, no hallaron una asociación significativa entre el subtipo de SII y la puntuación de EAT (p > 0,05). Sin embargo, la intensidad y la duración del SII presentaron una correlación positiva con las puntuaciones de EAT, lo que justifica algunos comentarios de otros autores en los que se vincula la presencia de SII con alimentación desordenada e incluso con trastornos alimenticios como anorexia nerviosa, bulimia y trastornos no especificados (44) .…”
Section: Recomendaciones Dietéticas En Síndrome De Intestino Irritableunclassified
“…Patients with DGBI often have eating-related concerns, and there is growing recognition of the relevance of DGBI symptoms to eating disorders (EDs). Both EDs and DGBIs lie at the interface of the brain-gut connection, with input from biological, psychological, and social factors [ 3 , 4 ].…”
Section: Introduction: Disorders Of Gut–brain Interaction and Eating ...mentioning
confidence: 99%
“…Patients with EDs frequently present with GI complaints, with patients with avoidant/restrictive food intake disorder (ARFID) showing particularly disproportionate GI symptom burden [ 13 , 14 ]. In inpatient and outpatient ED settings, DGBI rates range from 39% and up to 98% [ 4 , 15 ]. EDs may induce DGBI—while retrospectively reported, one study in irritable bowel syndrome (IBS) found that ED symptoms preceded IBS diagnosis for the majority (87%) of patients [ 16 ].…”
Section: Introduction: Disorders Of Gut–brain Interaction and Eating ...mentioning
confidence: 99%
See 1 more Smart Citation
“…The metabolism and digestion can be severely impacted by AN which leads to gastrointestinal (GI) complaints like postprandial distress or distension of the abdomen and stomach due to slow gastric motility [ 4 ] which could—at least in part—further contribute to the low food intake of these patients [ 5 ]. In addition, functional GI disorders are frequent in patients with AN [ 6 ]. Lastly, subjects with AN may eat less of a regularly composed meal but tend to choose foods with low energy density, fewer calories, but large volume, for example fruits and vegetables or settle on a vegetarian diet with a higher amount of carbohydrates than protein or fat [ 7 ].…”
Section: Introductionmentioning
confidence: 99%